Current Knowledge on Pancreatic Cancer - Iovanna, Juan; Mallmann, Maria C.; Goncalves, Anthony; Turrini, Olivier; Dagorn, Jean-Charles (Frontiers in Oncology, 2012)
Pancreatic cancer is the fourth leading cause of cancer death with a median survival of 6 months and a dismal 5-year survival rate of 3-5%. The development and progression of pancreatic cancer are caused by the activation of oncogenes, the inactivation of tumor suppressor genes and the deregulation of many signalling pathways. Therefore, the strategies targeting these molecules as well as their downstream signalling could be promising for the prevention and treatment of pancreatic cancer. However, although targeted therapies for pancreatic cancer have yielded encouraging results in vitro and in animal models, these findings have not been translated into improved outcomes in clinical trials. This failure is due to an incomplete understanding of the biology of pancreatic cancer and to the selection of poorly efficient or imperfectly targeted agents. In this review, we will critically present the current knowledge regarding the molecular, biochemical, clinical and therapeutic aspects of pancreatic cancer.